First Evidence of Individual Sharks Involved in Multiple Predatory Bites on People - Clua, Eric E. G.; Meyer, Carl G.; Freeman, Mark; Baksay, Sandra; Bidenbach, Hadrien; Haguenauer, Anne; Linnell, John D. C.; Séguigne, Clémentine; Surina, Steven; Vely, Michel; Vignaud, Thomas; Planes, Serge (Conservation letters, 2024)
ABSTRACT It is widely accepted that populations of terrestrial predators sometimes contain “problem individuals” that repeatedly attack humans, yet this phenomenon has never been demonstrated in sharks. Here, we present photographic and genetic evidence of individuals in populations of tiger Galeocerdo cuvier and oceanic whitetip Carcharhinus longimanus sharks that (1) demonstrated atypical behavior compared to the rest of the population, (2) engaged in repeated agonistic behavior directed toward humans, and (3) bit, or attempted to bite humans in probable foraging attempts. These case studies provide some of the first evidence for the existence of “problem individuals” among sharks. The percentage of fatalities due to the same shark individual are not known, so we recommend systematic swabbing of shark bite victims wounds to better understand the importance of this phenomenon and the possibility of identifying these animals. Environmentally conscientious management options for problem individuals range from prohibiting ocean activities (e.g., swimming and surfing) in their habitats to selectively removing the individual, although the latter would be challenging in the marine environment.